2022
DOI: 10.48550/arxiv.2202.08291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Microphysics of Early Dark Energy

Vivian I. Sabla,
Robert R. Caldwell

Abstract: Early Dark Energy (EDE) relies on scalar field dynamics to resolve the Hubble tension, by boosting the pre-recombination length scales and thereby raising the CMB-inferred value of the Hubble constant into agreement with late universe probes. However, the collateral effect of scalar field microphysics on the linear perturbation spectra appears to preclude a fully satisfactory solution. H0 is not raised without the inclusion of a late universe prior, and the "S8-tension", a discrepancy between early-and late-un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…In other words, data would be hinting at new physics not taken into consideration within the standard cosmological model [29][30][31]. For instance, a configuration of vector fields leading to an effective Early Dark Energy (EDE) fluid with equation of state w EDE (z), sound speed c 2 s,EDE , and non-vanishing anisotropic stress π EDE (z) could simultaneously soften H 0 and S 8 tensions [32].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, data would be hinting at new physics not taken into consideration within the standard cosmological model [29][30][31]. For instance, a configuration of vector fields leading to an effective Early Dark Energy (EDE) fluid with equation of state w EDE (z), sound speed c 2 s,EDE , and non-vanishing anisotropic stress π EDE (z) could simultaneously soften H 0 and S 8 tensions [32].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, EDE models tend to slightly increase the S 8 tensions [853,914] and can be constrained with the full shape of the galaxy power spectrum [915,916], although current data are inconclusive [887,[917][918][919]. Nevertheless, it is clear that EDE alone cannot resolve the S 8 tension, and would require a more complicated dynamics [891,920,921] or an independent mechanism [852][853][854]. Future data will play a crucial role in arbitrating the fate of the EDE scenario, as it has been shown that data from the AdvACT [909] or CMB-S4 [886] can unambiguously confirm (or exclude) the presence of an EDE that resolves the Hubble tension in the early-universe.…”
Section: Ingmentioning
confidence: 96%
“…Allali et al 2021;Ye et al 2021;Clark et al 2021). Massive neutrinos are an economical and conservative candidate in this sense, as we know from oscillation experiments at least two neutrino mass eigenstates 2022); Sabla & Caldwell (2022). 2 In the above, the CMB data is from Planck.…”
Section: Ede and Massive Neutrinosmentioning
confidence: 99%